Research and Application of Mobile OA Technology in Power Generation Enterprise - Zheng Liu; Jing Wang (Dianxin kexue)
As the rapid development of mobile Internet and cloud computing technology, enterprise mobile OA needs bred. Using the CPI group mobile OA system construction project as a case, the existing various technical routes were researched in-depth. Combining the mature page adaptation techniques with VPN, authentication system and mobile device management system, a method to build mobile OA platform architecture was proposed and strictly controlled class 2 of information system level protection to building the security system, and the mobile OA system can deliver the best user experience under the premise of information security.